Ефективне навчання англійської мови дистанційно - Постоленко, Ірина (Studies in Comparative Education, 2015)
У статті розглянуто питання ефективного навчання англійської мови дистанційно. Досліджено організаційно-педагогічні підходи до ефективного дистанційного навчання. Обґрунтовано ефективні методи, форми та засоби дистанційного навчання. Проаналізовано наукові погляди щодо особливостей сприйняття навчального матеріалу студентами. Охарактеризовано основні проблеми та труднощі, які виникають у викладачів та студентів під час навчання англійської мови дистанційно. В статье рассмотрены вопросы эффективного обучения английскому языку дистанционно. Исследуются подходы к эффективному дистанционному обучению. Обоснованно методы, формы и средства дистанционного обучения. Проанализированы теоретические взгляды относительно особенностей восприятия учебного материала студентами. Охарактеризованы основные проблемы и сложности, которые возникают у преподавателей и студентов при обучении английскому языку дистанционно. The article analyzes the questions of effective distance learning of English. The main approaches to effective distance education are investigated. The methods, forms and means of distance learning are approved. The article describes theoretical views on perception of educational material by students. The characteristics of the main problems and difficulties that teachers and students face while distance learning of English are given. Modern educational institutions are increasingly appealing to online distance learning courses to save time and study areas. Training programs based on the use of the Internet does not require the use of classrooms for training, they can be accessed at any time, and allow students and instructors to work independently. Despite these advantages, there are many problems associated with these courses, which potentially affect their successful implementation. Distance courses and hybrid (mixed) courses are often combined, but they may vary and should be distinguished. When we talk about distance learning courses, or in other words, online courses, we mean courses that have no direct interaction between instructor and student. The interaction between them and the learning process is achieved with the help of various technological tools. Hybrid courses which can also be called mixed courses rates vary considerably from distance learning courses, as they present a direct interaction between participants in the learning process. It is important to note that for distance learning courses general education management system is required, and course management systems accommodate the desired content (e.g., Blackboard, Moodle, and Sakai). In addition, such systems sometimes even have a website, Wikipedia, forum or blog. Both instructors and students can use the downloaded content, talk to each other, and correspond through instant messaging, email and telephone communications.